Unmasking the hidden dangers in caesarean scar pregnancy: a case series - Manju R.; Geetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Caesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy with increasing incidence due to rising caesarean section rates. This case series aims to describe the clinical presentation, diagnostic approach, management, and outcomes of patients with caesarean scar pregnancies managed at our institution. This retrospective case series included eight patients diagnosed with caesarean scar pregnancy at Sri Ramachandra Institute of Higher Education and Research over a two-year period (January 2023–January 2025). Diagnosis was based on established ultrasonographic criteria. Clinical presentation, management strategies, and outcomes were analyzed. All patients had a history of prior caesarean deliveries. The majority presented with vaginal bleeding in early pregnancy, while one patient was diagnosed incidentally. Transvaginal ultrasound confirmed caesarean scar implantation in all cases. Management included systemic and intrasac methotrexate administration, ultrasound-guided suction evacuation, and uterine artery embolization in selected cases. Serial β-hCG monitoring guided treatment response. Fertility-preserving conservative management was successful in all patients without major complications. Early diagnosis and individualized conservative management can result in favourable outcomes in caesarean scar pregnancy. Increased awareness, early imaging, and careful monitoring are critical to prevent life-threatening complications and preserve reproductive potential. Further studies are needed to establish standardized treatment guidelines.